sosialisasi gerakan semangat menabung sejak dini serta mengedukasi perbedaan antara kebutuhan dan keinginan - Zizoya Rahmalia; Agus Suriadi (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The Covid-19 pandemic provides an important lesson in financial management, namely the need for the ability to distinguish between needs and desires. If the need is something that is really needed by humans, desire refers more to the feeling of wanting to have something both soon and that will date. Therefore it is necessary to save money so that it can be a savior when we experience financial difficulties, activities from an early age are important for children aged 5-12 years to build the habit of spending some of their pocket money. This is considering that the consumptive behavior of the Indonesian people continues to increase every year. Therefore, it is necessary to socialize the movement of the spirit of saving from an early age which is carried out to the children of the Puteri Aisyiyah Orphanage. The program intervention used in this practicum is the Mezzo Intervention by Zastrow which consists of Intake / Contract, Assessment, Program Planning, Formulation & Action Plan Phase, Implementation, Evaluation and Termination.